Abordagem experimental para aulas de circuitos de corrente contínua utilizando placa protoboard em turmas do ensino médio - Sousa, José Alisson Freitas de (Universidade Federal Rural do Semi-Árido, 2018)
This work presents a proposal for an experimental approach to the teaching of electrical circuits, using a Protoboard board and simple elements like LEDs and a multimeter, approached in High School. It aims at complementing the theoretical part using resources at affordable prices and addressing the full extent of this content. One of its advantages is because it can be compact, it can be taken to any location and its demonstration possible in any place, which is ideal for schools that do not have a laboratory or when it is not functional. During the conduction of production and application of the material we could see beyond the improvement of class performance an increase in the motivation of students and teachers for the subjects discussed. This result was obtained through the application of several practices involving more than one hundred students and a research with eight teachers working in public schools in the state of Ceará and Rio Grande do Norte.
Keywords: Professores; Experimentos; Baixo custo; Física; Eletricidade; Professores; Experimentos; Baixo custo; Física; Eletricidade; CIENCIAS EXATAS E DA TERRA::FISICA